The risk of post-polypectomy bleeding among patients receiving antithrombotic agents: A prospective observational study - Bozkurt, Hilmi (2021)
BACKGROUND: In July 2012, the Japan Gastroenterological Endoscopy Society updated their guidelines for gastroenterological endoscopy in patients receiving antithrombotic therapy. Colonoscopic polypectomy procedures are associated with a high risk of bleeding. OBJECTIVES: The present study evaluated the safety of colonoscopic polypectomy procedures in terms of bleeding, among patients receiving antithrombotic therapy. DESIGN AND SETTING: Prospective observational study conducted in a tertiary-level public cardiovascular hospital in Istanbul, Turkey. METHODS: Colonoscopic polypectomies carried out in a single endoscopy unit between July 2018 and July 2019 were evaluated prospectively. The patients’ data, including age, gender, comorbidities, whether antithrombotic drug use was ceased or whether patients were switched to bridging therapy, polyp size,polyp type, polyp location, histopathology, resection methods (hot snare, cold snare or forceps) and com- plications relating to the procedures were recorded. RESULTS: The study was completed with 94 patients who underwent a total of 167 polypectomy procedures. As per the advice of the physicians who prescribed antithrombotic medications, 108 polypectomy procedures were performed on 60 patients without discontinuing medication and 59 polypectomy procedures were performed on 34 patients after discontinuing medication. The age, gender distribution and rate of bleeding did not differ significantly between the patients whose medication was discontinued and those whose medication was continued (P > 0.05). CONCLUSION: This study found that the colonoscopic polypectomy procedure without discontinuation of antithrombotic medication did not increase the risk of bleeding. This procedure can be safely performed by experienced endoscopists in patients with an international normalized ratio (INR) below 2.5.